2022
DOI: 10.1111/emre.12510
|View full text |Cite
|
Sign up to set email alerts
|

Mapping crowdfunding in cultural and creative industries: A conceptual and empirical overview

Abstract: The landscape of cultural and creative industries (CCIs) has been changing strongly because of new players who have entered the arena by reshaping financing strategies. This work represents a first attempt to describe and compare the European population of crowdfunding platforms used by firms and creatives to launch cultural and creative projects. Specifically, we provide an assessment of how and where cultural crowdfunding platforms emerge. We also explore the extent to which government expenditures on cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The network impact is more present at the beginning and end of a campaign (Borst et al, 2018) since early contributions of "family and friends" are later replaced by loyal backers who care more about the content of the project than the creator (Skirnevskiy et al, 2017). This connects to the finding that social media is most effective at a campaign's beginning (Dehdashti et al, 2022) creator is important (Cicchiello et al, 2022) and often happens within the platform via comments and updates.…”
Section: Main Themesmentioning
confidence: 99%
See 1 more Smart Citation
“…The network impact is more present at the beginning and end of a campaign (Borst et al, 2018) since early contributions of "family and friends" are later replaced by loyal backers who care more about the content of the project than the creator (Skirnevskiy et al, 2017). This connects to the finding that social media is most effective at a campaign's beginning (Dehdashti et al, 2022) creator is important (Cicchiello et al, 2022) and often happens within the platform via comments and updates.…”
Section: Main Themesmentioning
confidence: 99%
“…Researchers explain that Twitter focuses on objective information and quality signals, while Facebook focuses on supporting connections and social norms. Moreover, to strengthen the connection, direct communication between the donor and project creator is important (Cicchiello et al, 2022) and often happens within the platform via comments and updates.…”
Section: Crowdfunding Features and Mechanisms Impacting Giving Behaviormentioning
confidence: 99%
“…The emergence of “participatory” digital platforms has caused major changes in CCIs in the last decade as new forms of online cultural participation (e.g. crowdfunding sites) have appeared (Cicchiello et al, 2022 ). In the face of the establishment of crowdfunding as a valid alternative or complementary mode of funding for cultural and creative projects and ventures, cultural policies can play a key role in helping legitimise this form of private financing and foster cultural participation through digital means (Casemajor et al, 2021 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In such circumstances, entrepreneurs typically fund their ventures by utilising their own capital, gathering funds from family and friends, in order to prove their ideas and cover early startup costs [9]. Social networks are considered a solution to early-stage financing gaps, assuming that online social networks enable new ventures to access a novel source, namely crowdfunding [10][11][12][13][14][15]. Shiller [16] suggested that new ventures can resolve their financial issues through an innovative method of securitization named equity crowdfunding.…”
Section: Introductionmentioning
confidence: 99%